2010
DOI: 10.1007/s11671-010-9763-2
|View full text |Cite
|
Sign up to set email alerts
|

Efficient Performance of Electrostatic Spray-Deposited TiO2 Blocking Layers in Dye-Sensitized Solar Cells after Swift Heavy Ion Beam Irradiation

Abstract: A compact TiO2 layer (~1.1 μm) prepared by electrostatic spray deposition (ESD) and swift heavy ion beam (SHI) irradiation using oxygen ions onto a fluorinated tin oxide (FTO) conducting substrate showed enhancement of photovoltaic performance in dye-sensitized solar cells (DSSCs). The short circuit current density (Jsc = 12.2 mA cm-2) of DSSCs was found to increase significantly when an ESD technique was applied for fabrication of the TiO2 blocking layer, compared to a conventional spin-coated layer (Jsc = 8.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
7
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 33 publications
(35 reference statements)
1
7
0
Order By: Relevance
“…The nanoclump formation, which depends on electrostatic spray conditions, may be explained due to the lower columbic force resulting from weak repulsion among adjacent droplets compared to the stretching force. 31 Recent observations by Hwang et al on electrostatic spray-deposited TiO 2 showed similar hierarchical TiO 2 clumps. 32 These authors claimed that the clumps or cluster-like spheres were formed by the ultrafast evaporation of a high vapour pressure solvent at the surface, generating high convection forces and consequently forming tight clusters.…”
Section: Resultsmentioning
confidence: 87%
“…The nanoclump formation, which depends on electrostatic spray conditions, may be explained due to the lower columbic force resulting from weak repulsion among adjacent droplets compared to the stretching force. 31 Recent observations by Hwang et al on electrostatic spray-deposited TiO 2 showed similar hierarchical TiO 2 clumps. 32 These authors claimed that the clumps or cluster-like spheres were formed by the ultrafast evaporation of a high vapour pressure solvent at the surface, generating high convection forces and consequently forming tight clusters.…”
Section: Resultsmentioning
confidence: 87%
“…These results suggest a rapid charge injection and transportation of photoexcited electrons in these bilayered architecture photoanode DSSCs. The main function of this under layer is to provide a compact layer/blocking layer for improving charge transport efficiency of the device reported frequently in many reports. , The bilayered DSSCs, SLP/TNF {111} -1 and SLP/TN {101} show power conversion efficiency of 9.15% and 7.59% respectively, due to improved J sc and V oc in these devices compared to single-layer DSSCs (TNF {111} -1 and TN {101} ).…”
Section: Resultsmentioning
confidence: 99%
“…The main function of this under layer is to provide a compact layer/blocking layer for improving charge transport efficiency of the device reported frequently in many reports. 52,53 The bilayered DSSCs, SLP/TNF {111} -1 and SLP/TN {101} show power conversion efficiency of 9.15% and 7.59% respectively, due to improved J sc and V oc in these devices compared to single-layer DSSCs (TNF {111} -1 and TN {101} ). Electrochemical impedance spectroscopy (EIS) measurements were conducted on symmetrical cells, and the results are plotted in the form of Nyquist plots (Figure 9).…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…The deposition methods for the com‐TiO 2 layer in PSCs are adapted from DSSCs and quantum‐dot‐sensitized solar cells (QDSSCs) but should be reoptimized for PSCs . For both architectures, the layer is primarily deposited by aerosol spray‐pyrolysis, though other methods are also used, for example spin coating, electrostatic spray deposition, chemical vapor deposition, thermal oxidation, electrochemical techniques, electrodeposition, and atomic layer deposition (ALD) . In PSCs, the impact of com‐TiO 2 film thickness has been studied to optimize device fabrication, often along with the comparison of different deposition techniques, showing that both thickness and deposition method can impact efficiency.…”
Section: Introductionmentioning
confidence: 99%